Notes on shark and ray types at the South China Sea Fisheries Research Institute (SCSFRI) in Guangzhou, China - White, William T.; Last, Peter R. (Zootaxa, 2013)
Most of the shark and ray type material at the South China Sea Fisheries Research Institute (SCSFRI) in Guangzhou, China was examined during a museum visit by the senior author in 2009. The status of the shark and ray species described from the South China Sea in the 1980s and deposited in this collection is discussed. Squalus acutirostris is considered a junior synonym of Squalus mitsukurii from the western North Pacific. Centrophorus ferrugineus is considered a junior synonym of Centrophorus squamosus. Centroscymnus macrops is confirmed as a junior synonym of Centroscymnus coelolepis. Scymnodon niger is confirmed as a junior synonym of Zameus squamulosus. Isistius labialis is considered a synonym of Isistius brasiliensis. Halaelurus immaculatus is confirmed as a valid species of the genus Bythaelurus. Urolophus marmoratus is considered a junior synonym of the widespread Plesiobatis daviesi. Springeria nanhaiensis is a questionable synonym of Sinobatis borneensis, following previous researchers. Springeria stenosoma is considered as questionably valid but with further investigation into generic placement required. The validity of species with SCSFRI type specimens not examined in this study are also briefly discussed.